Characterizing Exchange Rate Policy in East Asia: A Reconsideration - CHOW, Hwee Kwan (Institutional Knowledge at Singapore Management University, 2007)
Frankel and Wei (1994) developed and popularized a method for uncovering the implicit weights assigned to major international currencies constituting a currency basket. We extend the methodology in two dimensions: include regional competitive pressure and employ a vector autoregressive (VAR) model to overcome simultaneity bias. With these modifications, we confirm the prominent role of the US dollar in the exchange rate policy of East Asian economies beyond the short run. However, despite the high degree of commitment to nominal exchange rate stability prior to the crisis, fluctuations in most East Asian currencies are also significantly influenced by country specific shocks. The findings of the post-crisis period suggest that East Asian exchange rate regimes have become more diverse, with the crisis countries (except Malaysia) exercising even greater flexibility in their exchange rate management. Overall, there is weak evidence that the East Asian economies have been benchmarking their currencies towards regional competitors' currencies over the longer term.